If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5x = -2x + 12 Reorder the terms: 3 + -5x = 12 + -2x Solving 3 + -5x = 12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + -5x + 2x = 12 + -2x + 2x Combine like terms: -5x + 2x = -3x 3 + -3x = 12 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + -3x = 12 + 0 3 + -3x = 12 Add '-3' to each side of the equation. 3 + -3 + -3x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 12 + -3 -3x = 12 + -3 Combine like terms: 12 + -3 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| -5(7a-8)=-(1-5a)+1 | | 2x-24a=8x | | t^2+7t-18= | | 15-3n=15 | | 4(-2x+2)+8x=-(5x+7) | | 4x^2+8x-83=-6 | | 44-4*(5+3*2)= | | 4x+19-2x+19=6 | | 26900.694=2*3.14*17.1*17.1+2*3.14*17.1*h | | (3x+2)x=300 | | 5x+5x+10=700 | | 7(x-5)=6 | | H(t)=-16t^2+80t+9 | | 66.4mg= | | 2(x-100)+x+3(x-80)=2680 | | 6611.584=2*3.14*r*r+2*3.14*r*61.2 | | 1/3*x+2/6=5*x-2/3 | | 5-0.50x=12 | | x+72+35=180 | | 72+35=180 | | 10-2s=12r+2s | | f(x)=(x-4)(4-x) | | -4(-4+2v)=-20+v | | 3k^2+12k-29=7 | | 1/3x+2/6=5x-2/3 | | (7x+33)=(9x+7) | | 9=2r-5 | | 2x-29=93 | | 23x+5x=2x | | -4(-2x+2)+8x=-(5x+7) | | X-47=12 | | X+3=3+2(2+3x)-5x |